Case report of a rare case of Non-hodgkin Lymphoma presenting as sternal mass - Konwar, Nilotpal; Dutta, Aparna; Sharma, Adity; Saikia, Projnan (International Journal of Medical Research and Review, 2017)
Primary or metastatic tumors of the chest wall constitute 5% of all thoracic tumors and lymphoma comprises about 2% of all chest wall tumors. We report a case of a 23year old male presenting with anterior chest wall mass for the past 6 months which was slowly growing in size. There was no other symptoms of respiratory difficulty, cough, and hemoptysis. HRCT chest revealed soft tissue attenuated lesion in mid chest wall and infiltration to the anterior mediastinum with erosion of sternum and the 8th rib. FNAC of the site revealed Non-Hodgkin Lymphoma. Diagnosis is based on morphological features, FNAC, cell block.